OP16 Does ethnic diversity confer protective effects on population health? intra-UK comparisons of ethnicity and mortality. (September 2018) - Schofield, L; Walsh, D; Feng, Z; Buchanan, D; Dibbens, C; Erdman, J; Fishbacher, C; McCartney, G; Munoz-Arroyo, R; Whyte, B
Abstract : Background: The most likely underlying causes of the higher mortality in Scotland compared to England & Wales (E&W) and in Glasgow compared to Liverpool and Manchester have been identified recently as relating in large part to vulnerabilities created by adverse historical living conditions allied to detrimental political decision-making. However, it was also suggested that there is a protective effect in E&W and Manchester of greater ethnic diversity, given the latter's association with lower-than-expected mortality among UK populations. We sought to assess the extent to which Scotland's 'excess' mortality (i.e. beyond that explained by deprivation) was attenuated by adjusting for ethnic diversity. Methods: The Scottish Longitudinal Study (SLS) and the ONS Longitudinal Study of E&W were used. E-dataSHIELD methodology was applied to analyse the restricted access data. Risk of all-cause mortality (2001–2010) was compared between 35–74 year-old residents of Scotland and E&W, and between Glasgow and Manchester, using Poisson regression. Models adjusted for age, gender, socio-economic position (SEP) and an ethnicity*country of birth (CoB) interaction. CoB has been shown to be important in explaining differences in ethnic mortality related to the 'healthy migrant effect'. Results: 18% of the Manchester sample was classed as non-White compared to only 3% in Glasgow. The equivalent figures for E&W and Scotland were 10.4% and 1.2% respectively. The mortality Incident Rate Ratio (IRR) was 1.33 (95% CIs 1.13, 1.56) in Glasgow compared to Manchester. This reduced to 1.25 (95% CI 1.07 to 1.47) after adjustment for SEP, and further reduced to 1.20 (95% CI 1.02 to 1.42) after adjustment for ethnicity*CoB. The equivalent figures for Scotland compared to E&W were: 1.18 (95% CIs 1.16 to 1.21) overall, reduced to 1.08 (95% CIs 1.05 to 1.10) after adjustment for SEP, and then to 1.04 (95% CIs 1.02 to 1.07) after adjustment for ethnicity*CoB. Across all samples, Non-Whites born outside UK/ROI had a lower risk of mortality than Whites born in UK/ROI; however, among the Scottish samples only, non-Whites born in UK/ROI had a higher risk of mortality compared with Whites born in UK/ROI – IRR 1.77 (95% CIs 1.10 to 2.85) for Scotland, 3.10 (95% CIs 1.28 to 7.51) for Glasgow. Conclusion: The research supports the hypothesis that greater diversity in ethnicity and migration status plays a partial role in explaining Scottish excess mortality. In Glasgow's case, however, a large excess remains: thus previously articulated policy implications such as addressing poverty, vulnerability and inequality still apply. Further research is warranted into the relatively high mortality of non-Whites born in UK/ROI and resident in Scotland.